2019
DOI: 10.3390/cancers12010039
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Alterations during Development of Castration-Resistant Prostate Cancer Are Detected in Circulating Tumor Cells

Abstract: Development of castration-resistant prostate cancer (CRPC) is associated with alterations in gene expression involved in steroidogenesis and androgen signaling. This study investigates whether gene expression changes related to CRPC development can be identified in circulating tumor cells (CTCs). Gene expression in paired CTC samples from 29 patients, before androgen deprivation therapy (ADT) and at CRPC relapse, was compared using a panel including 47 genes related to prostate cancer progression on a qPCR pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Previous studies 19 , 37 have illustrated that intra-tumor heterogeneity is central to the biological behaviors of tumors. For instance, nearly all patients with metastatic prostate cancer patients will evitably progress to the castration-resistant stage after one or two years' endocrine therapy 11 . Also, the time to castration-resistant from the start of endocrine therapy remains diverse among different patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies 19 , 37 have illustrated that intra-tumor heterogeneity is central to the biological behaviors of tumors. For instance, nearly all patients with metastatic prostate cancer patients will evitably progress to the castration-resistant stage after one or two years' endocrine therapy 11 . Also, the time to castration-resistant from the start of endocrine therapy remains diverse among different patients.…”
Section: Discussionmentioning
confidence: 99%
“…The standard therapy for metastatic prostate cancer remains the androgen deprivation therapy (ADT). However, metastatic prostate cancer patients will inevitably progress to the castration-resistant stage after one or two years' ADT 11 . Moreover, the time to the castration-resistant stage from the beginning of receiving ADT in metastatic prostate cancer patients remains diverse among different patients 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent advancements in technologies for analyzing circulating tumor cells (CTC) could have a role by allowing the serial sampling of cancer-derived cells over time. Several groups have reported sequencing analyses of CTCs that demonstrate the complex and heterogeneous tumor biology of metastatic PCa in men treated with ADT and identify gene alterations during the development of CRPC [ 29 , 30 , 31 ]. Other sequencing approaches, such as the analysis of cell-free DNA for mutations, structural alterations, and methylation, could also be used to understand and predict the transition from the hormone-naïve to the resistant state [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study also indicated that one of the PCS subtypes similarly reflects enzalutamide resistance [ 80 ]. Some studies have also reported that midkine (MDK) is a chemokine that is upregulated in CRPC, and a research group found that elevated MDK expression on CTCs in metastatic hormone-sensitive prostate cancer (mHSPC) was significantly correlated with poor cancer-specific survival (CSS) [ 81 ]. They emphasized the potential role of MDK expression on CTCs for the study of resistance mechanisms.…”
Section: Treatment Guidancementioning
confidence: 99%